Wilhelm Windelband und die Psychologie Das Fach Philosophie und die Wissenschaft Psychologie im Deutschen Kaiserreich - Gundlach, Horst (Heidelberg University Publishing (heiUP), 2017)
Wilhelm Windelband (1848-1915) was a professor of philosophy during the German Empire, leader of the south-west German school of neo-Kantianism and an influential, when somewhat opinionated, public speaker. Neo-Kantianism was linked with opposition to the discipline of psychology and Windelband is noted in the history of science as nurturing a pronounced dislike of psychology, and of expressing this opinion polemically. The reality, presented here for the first time, looks different. He championed at an early stage the independence of psychology, worked on a book about psychology and gave more than twenty lectures about psychology. The institutional background concerning the difficult relationship between philosophy and psychology is examined, and shows that Windelband was not an isolated case in the history of philosophy.